How combined aerobic training and pomegranate juice intake affect lipid profile? A clinical trial in men with type 2 diabetes - Nemati Sasan; Tadibi Vahid; Hoseini Rastegar (Sciendo, 2021)
Study aim: This study aimed to investigate the effect of aerobic training (AT) and pomegranate juice intake (PJI) on the lipid profile in men with type 2 diabetes.